METHODS OF USING STANDARDS IN SOFTWARE DESIGN (American Journal of Technology and Applied Sciences, 2023)
The exponential growth of mobile communication tools has necessitated the development of robust software testing methodologies to ensure the reliability, usability, and security of these tools. This abstract provides an overview of the methods used to test software tools on users of mobile communication tools, drawing from a comprehensive literature review.